Kuulutan suuruutesi - Saalem House Band; Laine, Jarkko (muusikko); Laine, Jukka; Lehikoinen, Mari; Lohelainen, Osku; Nieminen, Elina; Rajala, Nina; Selkälä, Tanja (Saalem House Band, 2012)
16 kappaletta.